Innovations in Manufacturing for Sustainability - Gupta, Kapil (Materials Forming, Machining and Tribology, 2019)
This book provides details on the innovations made to achieve sustainability in manufacturing. It highlights the trends of current progress in research and development being done to achieve overall sustainability in manufacturing technology. Green-EDM, Hybrid machining, MQL assisted machining, sustainable casting, welding, finishing and casting, energy- and resource-efficient manufacturing are some of the important topics discussed in this book.